2017
DOI: 10.1051/e3sconf/20172200139
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in quality of wastewater from fruit and vegetable industry

Abstract: Abstract. The paper aimed at evaluating the seasonal changes in quality of wastewater from facilities producing fruit and vegetable juices, processed and frozen products, and vegetable concentrates. The study revealed that wastewater from fruit and vegetable industry contain large amounts of organic substances expressed as BOD5 (minimum -500 mgO2/dm 3 , maximum -6 100 mgO2/dm 3 ) and COD (minimum -806 mg O2/dm 3 , maximum -7 732 mg O2/dm 3 ), while is deficient in nitrogen and phosphorus. Considerable seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…An investigation of 11 FVPI units was conducted, and the results showed that water consumption and wastewater generation reached 1.8 × 10 5 to 6.0 × 10 5 m 3 /year and 130 to 330 m 3 /hr, respectively (Valta et al., ). Wastewater contains large amounts of organic substances expressed as 5‐day biochemical oxygen demand (BOD 5 ) (500 to 6100 mg/L) and COD (806 to 7732 mg/L), indicating a serious environmental problem (Puchlik & Ignatowicz, ) and requiring a high cost for water treatment as shown in Table . Therefore, the removal of these bioactive substances is a challenge in the wastewater treatments.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of 11 FVPI units was conducted, and the results showed that water consumption and wastewater generation reached 1.8 × 10 5 to 6.0 × 10 5 m 3 /year and 130 to 330 m 3 /hr, respectively (Valta et al., ). Wastewater contains large amounts of organic substances expressed as 5‐day biochemical oxygen demand (BOD 5 ) (500 to 6100 mg/L) and COD (806 to 7732 mg/L), indicating a serious environmental problem (Puchlik & Ignatowicz, ) and requiring a high cost for water treatment as shown in Table . Therefore, the removal of these bioactive substances is a challenge in the wastewater treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Until 2015, about 1200 farms dealing with cattle breeding, 3000 farms dealing with pig breeding, and 3500 farms dealing with poultry were registered in Poland-a total of 7800 farms with livestock density above 100 LU, where biogas production is possible, technically justified, and economical [10]. It results, among others, from this branch structure in Poland that is characterized by a great degree of fragmentation [11].…”
Section: Introductionmentioning
confidence: 99%